2008
DOI: 10.1111/j.1469-185x.2008.00055.x
|View full text |Cite
|
Sign up to set email alerts
|

Ossification patterns in the tetrapod limb – conservation and divergence from morphogenetic events

Abstract: Two different patterns of the condensation and chondrification of the limbs of tetrapods are known from extensive studies on their early skeletal development. These are on the one hand postaxial dominance in the sequential formation of skeletal elements in amniotes and anurans, and on the other, preaxial dominance in urodeles. The present study investigates the relative sequence of ossification in the fore- and hindlimbs of selected tetrapod taxa based on a literature survey in comparison to the patterns of ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
72
0
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 77 publications
(80 citation statements)
references
References 89 publications
5
72
0
3
Order By: Relevance
“…Variation within urodeles appears to exceed that seen in other clades of tetrapod (Shubin and Alberch, 1986;Blanco and Alberch, 1992;Vorobyeva and Hinchliffe, 1996;Shubin and Wake, 2003;Franssen et al, 2005;Fröbisch, 2008).…”
Section: Developmentmentioning
confidence: 99%
See 3 more Smart Citations
“…Variation within urodeles appears to exceed that seen in other clades of tetrapod (Shubin and Alberch, 1986;Blanco and Alberch, 1992;Vorobyeva and Hinchliffe, 1996;Shubin and Wake, 2003;Franssen et al, 2005;Fröbisch, 2008).…”
Section: Developmentmentioning
confidence: 99%
“…The ontogenetic series for the branchiosaurid Apateon is extraordinary in its completeness, but can only provide insights into the sequence of ossification rather than earlier events in skeletogenesis, because only bony tissues are fossilized. Nevertheless, it has been demonstrated that although ossification is not a recapitulation of the sequence of events in early skeletogenesis, the general direction and polarity of digit development is preserved in the ossification sequence, with a close correlation in particular in anamniotes (Fröbisch, 2008). The ossification sequence can therefore provide insights into the early patterning of the limbs of this extinct clade despite the fact that the sequence of chondrogenesis, being of soft tissue, cannot be preserved.…”
Section: What the Fossils Tell Usmentioning
confidence: 99%
See 2 more Smart Citations
“…If preserved, they provide valuable insight into the life history of extinct taxa, as well as evolutionary trajectories. To date, ossification sequences in fossils are available for some "fish" (Cloutier, 2010), temnospondyl and lepospondyl amphibians (Fröbisch, 2008;Fröbisch et al, 2010Fröbisch et al, , 2015, "younginiforms" (sensu Bickelmann et al, 2009) (Currie, 1981;Caldwell, 2002), mosasaurs (Caldwell, 2002), sauropterygians (Hugi and Scheyer, 2012), ichthyosaurs (Caldwell, 1997), sauropsids (Delfino and Sánchez-Villagra, 2010) and mammals (Sánchez-Villagra, 2010). Most of this information is derived from secondarily aquatic taxa, which is the result of a taphonomic bias (Fröbisch et al, 2010).…”
Section: Introductionmentioning
confidence: 99%